Loss of C-Terminal Coiled-Coil Domains in SDCCAG8 Impairs Centriolar Satellites and Causes Defective Sperm Flagellum Biogenesis and Male Fertility - Kecheng Li; Xiaoli Zhou; Wenna Liu; Yange Wang; Zilong Zhang; Houbin Zhang; Li Jiang (Cells)
Sperm flagellum defects are tightly associated with male infertility. Centriolar satellites are small multiprotein complexes that recruit satellite proteins to the centrosome and play an essential role in sperm flagellum biogenesis, but the precise mechanisms underlying this role remain unclear. Serologically defined colon cancer autoantigen protein 8 (SDCCAG8), which encodes a protein containing eight coiled-coil (CC) domains, has been associated with syndromic ciliopathies and male infertility. However, its exact role in male infertility remains undefined. Here, we used an Sdccag8 mutant mouse carrying a CC domains 5–8 truncated mutation (c.1351–1352insG p.E451GfsX467) that models the mutation causing Senior–Løken syndrome (c.1339–1340insG p.E447GfsX463) in humans. The homozygous Sdccag8 mutant mice exhibit male infertility characterized by multiple morphological abnormalities of the flagella (MMAF) and dysmorphic structures in the sperm manchette. A mechanistic study revealed that the SDCCAG8 protein is localized to the manchette and centrosomal region and interacts with PCM1, the scaffold protein of centriolar satellites, through its CC domains 5–7. The absence of the CC domains 5–7 in mutant spermatids destabilizes PCM1, which fails to recruit satellite components such as Bardet–Biedl syndrome 4 (BBS4) and centrosomal protein of 131 kDa (CEP131) to satellites, resulting in defective sperm flagellum biogenesis, as BBS4 and CEP131 are essential to flagellum biogenesis. In conclusion, this study reveals the central role of SDCCAG8 in maintaining centriolar satellite integrity during sperm flagellum biogenesis.